Patterns of protein expression in human head and neck cancer cell lines differ after proton vs photon radiotherapy. Issue 2 (11th November 2019) - Wang, Li; Yang, Liuqing; Han, Shichao; Zhu, Jinming; Li, Yuting; Wang, Zeming; Fan, You‐Hong; Lin, Eric; Zhang, Ruiping; Sahoo, Narayan; Li, Yupeng; Zhang, Xiaodong; et al.
Abstract: Background: Proton radiotherapy (PRT) may be a less toxic alternative to photon radiotherapy (XRT) for patients with head and neck squamous cell carcinoma (HNSCC). However, the molecular responses of HNSCC cells to PRT vs XRT are unclear. Methods: Proteomics analyses of protein expression profiles by reverse‐phase protein arrays were done for two human papillomavirus [HPV]‐negative and two HPV+ cell lines. Expression patterns of 175 proteins involved in several signaling pathways were tested. Results: Compared with PRT, XRT tended to induce lower expression of DNA damage repair—and cell cycle arrest‐related proteins and higher expression of cell survival‐ and proliferation‐related proteins. Conclusions: Under these experimental conditions, PRT and XRT induced different protein expression and activation profiles. Further preclinical verification is needed, as are studies of tumor pathway mutations as biomarkers for choice of treatment or as radiosensitization targets to improve the response of HNSCC to PRT or XRT.